Unit Kesihatan UiTM (Perak) appointment scheduling system using Genetic Algorithm (GA) / Nur Amiera Abdul Rahman - Abdul Rahman, Nur Amiera (2014)
Alhamdulillah, my heartfelt thanks and gratitude to Allah SWT, that he was willing to give a chance with the good health and leisure time to complete this final year project proposal titled Unit Kesihatan UiTM (Perak) Appointment Scheduling System Using Genetic Algorithm (GA). The final year project has been properly drawn for Universiti Teknologi Mara (UiTM), basically for the students to complete the degree program leading to a Bachelor of Science (Hons) in Computer Science. First and foremost, l would like to thank Mrs. Siti Khatijah Nor Binti Abdul Rahim as a lecturer for the subject of Project Formulation CSP600, Mr. Mohamed lmran Mohamed Ariff as a lecturer for the subject Project CSP650. I also wish to thank the project supervisor, Mr Ahmad Farid Bin Najmuddin for his supervision of the work done for this project proposal. He also passed on a lot of knowledge, experience and share ideas for the project and takes the time to improve the lack of projects. Special appreciation also goes to my beloved mother, Normah binti Samah for her patience, supportive words and devotion that give me the strength to carry out this research. I am grateful and thankful to my family for the support and motivation and prepared the funding for me during my studies. Last but not least, my highest gratitude to my classmates who had helped me during the project preparation.